An evaluation of e-government within the Provincial Government Western Cape (PGWC) - Jantjies, Stephan Omar (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPA (Public Management and Planning))--University of Stellenbosch, 2010.